2007
DOI: 10.1021/jf070019m
|View full text |Cite
|
Sign up to set email alerts
|

Myowater Dynamics and Protein Secondary Structural Changes As Affected by Heating Rate in Three Pork Qualities:  A Combined FT-IR Microspectroscopic and 1H NMR Relaxometry Study

Abstract: The objective of this study was to investigate the influence of heating rate on myowater dynamics and protein secondary structures in three pork qualities by proton NMR T2 relaxation and Fourier transform infrared (FT-IR) microspectroscopy measurements. Two oven temperatures at 100 degrees C and 200 degrees C corresponding to slow and fast heating rates were applied on three pork qualities (DFD, PSE, and normal) to an internal center temperature of 65 degrees C. The fast heating induced a higher cooking loss, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 36 publications
6
26
1
Order By: Relevance
“…The protein secondary structural changes observed upon heating (increase in b-sheet structure) are consistent with literature references (Bouraoui et al, 1997;Moosavi-Nasab, All, Ismail, & Ngadi, 2005;Sánchez-González et al, 2008;Herrero et al, 2008b). In this connection, FT-IR spectroscopic studies in meat myofibrillar proteins have shown that the levels of b-sheet structures increase upon heating (Wang & Smith, 1994;Kirschner, Ofstad, Skarpeid, Hp~st, & Kohler, 2004;Böcker, Ofstad, Bertram, Egelandsdal, & Kohler, 2006;Wu et al, 2006;Wu, Bertram, Böcker, Ofstad, & Kohler, 2007). In myofibrillar proteins, complete protein denaturation and aggregation upon heat- 1.…”
Section: Raman Spectroscopic Analysismentioning
confidence: 99%
“…The protein secondary structural changes observed upon heating (increase in b-sheet structure) are consistent with literature references (Bouraoui et al, 1997;Moosavi-Nasab, All, Ismail, & Ngadi, 2005;Sánchez-González et al, 2008;Herrero et al, 2008b). In this connection, FT-IR spectroscopic studies in meat myofibrillar proteins have shown that the levels of b-sheet structures increase upon heating (Wang & Smith, 1994;Kirschner, Ofstad, Skarpeid, Hp~st, & Kohler, 2004;Böcker, Ofstad, Bertram, Egelandsdal, & Kohler, 2006;Wu et al, 2006;Wu, Bertram, Böcker, Ofstad, & Kohler, 2007). In myofibrillar proteins, complete protein denaturation and aggregation upon heat- 1.…”
Section: Raman Spectroscopic Analysismentioning
confidence: 99%
“…In addition, fast heating was reported to cause severe myofibrillar shortening and decreased sarcomere length and this was associated to higher cooking loss (King et al, 2003). Recently, relations between heating rates, cooking losses and protein changes were more completely established on pork also at a secondary protein structure level by means of combined FT-IR spectroscopy and low-field NMR relaxometry, as higher water depletion induced by faster heating was found to lead to random structure and aggregated b,-sheet as well lower content of a-helical structures (Wu et al, 2007). Thus, it is possible to hypothesize that pork samples showing the highest water loss could be probably subjected to the highest degree of protein denaturation.…”
Section: Meat Texturementioning
confidence: 99%
“…[12] NMR spectroscopy has been used to measure the water activity in meat as the shape of the T 2 relaxogram is closely linked to changes in the state or structure of water in meat. [15][16][17][18] 1 H-NMR spin-spin relaxation studies have shown that there are ''restricted water'' and ''strongly restricted water'' in living cells. [19][20][21][22] Both types of water possess different dynamic behavior in terms of mobility.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%